2016
DOI: 10.1111/exd.12889
|View full text |Cite
|
Sign up to set email alerts
|

Is the eccrine gland an integral, functionally important component of the human scalp pilosebaceous unit?

Abstract: The pilosebaceous unit (PSU) and the eccrine sweat gland (ESG) are classically described as completely independent skin appendages. However, careful inspection of scalp follicular units reveals that the secretory segment of the ESG spatially approximates the hair follicle in a position below the sebaceous gland and the insertion of the arrector pili muscle. Therefore, we propose here that, contrary to conventional wisdom, the PSU and the ESG should not be viewed in isolation, and may form instead, along with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
3
16
0
Order By: Relevance
“…However, when following the whole trajectory of the ESG from the skin surface to the hypodermis, we recently observed that the secretory coiled portion of most ESGs progressively moves closer to the HF and becomes spatially closely associated with it . In the current study we have therefore systematically followed up the hypothesis that these ESGs actually form an integral component of the PSU, using a three‐dimensional (3D) reconstruction methodology on human scalp skin sections, and observation of follicular unit (FU) transplant grafts and intravital dye staining of whole‐mount human‐scalp skin strips ex vivo .…”
mentioning
confidence: 96%
“…However, when following the whole trajectory of the ESG from the skin surface to the hypodermis, we recently observed that the secretory coiled portion of most ESGs progressively moves closer to the HF and becomes spatially closely associated with it . In the current study we have therefore systematically followed up the hypothesis that these ESGs actually form an integral component of the PSU, using a three‐dimensional (3D) reconstruction methodology on human scalp skin sections, and observation of follicular unit (FU) transplant grafts and intravital dye staining of whole‐mount human‐scalp skin strips ex vivo .…”
mentioning
confidence: 96%
“…Each eccrine sweat gland consists of a secretory coil deep in the dermis and a duct that conveys the secreted sweat to the skin surface. Traditionally, the sweat gland is viewed as anatomically separate from the pilosebaceous unit; however, a recent morphological study suggests a much closer physical association with the HF, with the secretory coil consistently situated below the insertion of the arrector pili muscle close to the outer root sheath [8]. The primary function of the eccrine unit is thermoregulation, which is accomplished through the cooling effects of evaporation of sweat from the skin's surface.…”
Section: Discussionmentioning
confidence: 99%
“…Although autophagy has been linked to lipodystrophy in adipocytes differentiated from murine embryonic fibroblasts and in human skin fibroblasts, previous research has failed to consider lipophagy as a possible mechanism within mature DAs. In this context, it may be productive to examine DAs surrounding human hair follicles (HFs), including the stem cell–rich bulge area . While DAs undergo size oscillations during synchronized murine HF cycling, being larger in anagen, it remains unknown whether human DAs undergo changes in cell size during the anagen‐catagen transition.…”
Section: Premisesmentioning
confidence: 99%